The dynamics of glocalization : the case of McDonald’s Portugal - Oliveira, Manuela Souza Constantino (2015)
Global corporations have searched for alternatives in order to protect their market shares in challenging environments where the benefits of standardization in its pure form are no longer enough to guarantee it. In this context, glocalization - that is, a mix between global standardization and local adaptation - is becoming a trend. This dissertation thus aims to understand the dynamics of the implementation of glocalization strategies and its impact at different market levels. The paper revolves around the case of the biggest global brand in the foodservice sector, which has been a sound example of pure standardization for decades, by exploring the case of McDonald’s Portugal and its glocal initiatives. The case provides the reader with information on how the company deals with glocalization and its challenges from headquarters to local restaurants. A primary market research adds to the paper through the analysis of the impact of glocal initiatives on consumers’ perceptions and attitudes from global to local levels. At last, glocal initiatives have produced a homogeneous impact on consumers at global level, whereas significant differences arise in regard to consumers’ perceptions, attitudes and the importance given to distinct marketing variables at different market levels, allowing a more effective relationship with the local market while preserving the global brand identity.